Wylie-Johnson analysis of adolescents of Afro-Brazilian descent with normal occlusion: investigation of the mean values - LORENZI,Lígia Maria (2014)
OBJECTIVE: The purpose of this study was to evaluate mean cephalometric measurements for a group of individuals of Afro-Brazilian descent using the Wylie-Johnson analysis, and to investigate the presence of sexual dimorphism. METHODS: Thirty-six lateral radiographs of the head of African-Brazilians were used. Subjects were 10 to 14 years old and had clinically normal occlusion, all permanent teeth, and no history of orthodontic treatment. RESULTS: Results for girls and boys were, respectively: SNA 88.31º and 89.68º; SNB 83.96º and 85.01º; ANB 4.44º and 4.69º; 1:1= 118.18º and 116.51º; FG-ST 16.47 mm and 16.12 mm; ST-Pmf 19.69 mm and 19.88 mm; Pmf-ANS 53.69 mm and 54.84 mm; Pmf-1ºMS 21.83 mm and 20.64 mm; FG-Pg 108.19 mm and 108.45 mm; FPL -MPL 27.48º and 27.65º; TAFH 111.06 mm and 112.26 mm; UAFH 45.26 mm and 45.38 mm; LAFH 65.80 mm and 66.88 mm; FG-FPL 1.069 mm and -2.086 mm; MBL 70.24 mm and 69.67 mm; MRH 51.89 mm and 53.70 mm; gonial angle 129.27º and 129.28º. Results of Student's-t test (α=5%) did not show any sexual dimorphism. Results of descriptive statistics were similar for the individuals of Afro-Brazilian descent in the study. CONCLUSION: Individuals of African descent had bimaxillary protrusion, a more acute interincisal angle, a larger inferior facial height, and a markedly convex profile.